Effect of fluoro-substituted acceptor-based ancillary ligands on the photocurrent and photovoltage in dye-sensitized solar cells. (15th March 2020) - Ashraf, Saba; Su, Rui; Akhtar, Javeed; Siddiqi, Humaira M.; Shuja, Ahmed; El-Shafei, Ahmed
Graphical abstract: Highlights: It is the first time to systematically study the acceptor-based ancillary ligand for Ru(II) sensitizers. Ru(II) sensitizers, SD7-SD10, were synthesized using fluoro-substituted electron acceptor ancillary ligands. The highest JSC (19.57 mA∙cm −2 ) and photovoltaic performance were observed for device employing sensitizer SD-7 . SD-8 (8.17%) outperformed the benchmark N719 (7.70%) in the overall solar to electric conversion efficiency. Abstract: Herein, we report four novel heteroleptic ruthenium (II) complexes, namely SD-7 to SD-10, containing fluoro- and trifluoro- methyl antennas as substituents on the ancillary ligands for dye-sensitized solar cells, and were compared to the benchmark dye N719. Photosensitizers (dyes) SD-7 to SD-10 were synthesized according to a typical one-pot three-step procedure with the corresponding ancillary ligands (LS-7 to LS-10). All the dyes were characterized by ATR-FTIR, 1 H NMR and mass spectrometry. Furthermore, the photophysical, electrochemical and photovoltaic performances were compared with N719. The band gaps, ground and excited state oxidation potentials were measured. The photovoltaic performance of the dyes showed that SD-7 with five fluorine atoms and SD-8 with CF3 at the – ortho position of the phenyl moiety outperformed the benchmark dye N719 with the efficiencies of 8.03% and 8.17%, respectively, with current density of 19.57 and 19.46 mA∙cm −2, respectively, and open-circuit voltages of 0.65 V and 0.69 V, respectively, under optimized conditions. The fabricated solar devices at lab-scale showed a systematic trend of decreasing JSC when the fluoro-substituted dyes were sensitized on TiO2 : SD-7 (with five –F) > SD-8 (with one CF3 at ortho position) > SD-9 (with one CF3 at para position) > SD-10 (with two CF3, one at ortho and one at para position). This can be attributed to the greater number of fluorine atoms directly attached to sp 2 hybridized carbon atoms, which greatly enhanced the dipole moment and intimate electronic coupling of SD-7 with TiO2 nanoparticles leading to better photocurrent density.